Nematicidal effects of cysteine proteinases against sedentary plant parasitic nematodes - Stepek, Gillian; Curtis, R.H.C.; Kerry, B.R.; Shewry, P.R.; Clark, S.J.; Lowe, Ann; Duce, I.R.; Buttle, David J.; Behnke, J.M. (Cambridge University Press, 2007)
Cysteine proteinases from the fruit and latex of plants, such as papaya, pineapple and fig, have previously been shown to have substantial anthelmintic efficacy, in vitro and in vivo, against a range of animal parasitic nematodes. In this paper, we describe the in vitro effects of these plant extracts against 2 sedentary plant parasitic nematodes of the genera Meloidogyne and Globodera. All the plant extracts examined caused digestion of the cuticle and decreased the activity of the tested nematodes. The specific inhibitor of cysteine proteinases, E-64, blocked this activity completely, indicating that it was essentially mediated by cysteine proteinases. In vitro, plant cysteine proteinases are active against second-stage juveniles of M. incognita and M. javanica, and some cysteine proteinases also affect the second-stage juveniles of Globodera rostochiensis. It is not known yet whether these plant extracts will interfere with, or prevent invasion of, host plants.